THE INFLUENCE OF FINANCIAL LITERACY, FINANCIAL TECHNOLOGY, AND FINANCIAL ATTITUDE ON FINANCIAL INCLUSION IN JAKARTA - Hendra, Martin; Tannia, Tannia (International Journal of Application on Economics and Business, 2025)
The purpose of this study is to ascertain and examine how financial technology, financial attitude, and financial literacy affect financial inclusion in Jakarta. Using a quantitative methodology and primary data, this study employs a questionnaire as its instrument and a Likert scale as its measuring tool. This study employs one dependent variable, financial inclusion, and three independent variables: financial literacy, financial technology, and financial attitude. The study's population consisted of all the people of Jakarta between the ages of 18 and 25. Purposive sampling and the hairs approach are used in this sample procedure. The hypothesis test, a validity test, and a reliability test are the data analysis methods employed. The data is then processed using SmartPLS.